2003
DOI: 10.1108/07378830310509727
|View full text |Cite
|
Sign up to set email alerts
|

Hand‐held computers in the classroom and the library: teaching and learning resource issues resulting from widespread deployment at the University of Minnesota Duluth

Abstract: The University of Minnesota Duluth (UMD) began requiring all incoming freshmen in computer science and engineering disciplines to purchase hand-held computers in the Fall of 2001. This article describes how the initiative was implemented and the effects it had on the structure of the teaching and learning environment at UMD. Special attention is paid to its impact on library concerns and the evolution of the relationship between hand-held computers and electronic reference material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…He also noted "You can put a novel into a PDA but the fact that one printed page will now amount to 5 þ screens may dampen your enthusiasm." Several authors discuss the challenges of providing support for PDAs (Peters et al, 2003;Garrison et al, 2003;Deneen and Arrert, 2003;Spires, 2008;Shipman and Morton, 2001). Deneen and Arrert (2003) note specific challenges to overcome in providing support including, providing a robust wireless infrastructure, the need for students to purchase additional software, and university provided training.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…He also noted "You can put a novel into a PDA but the fact that one printed page will now amount to 5 þ screens may dampen your enthusiasm." Several authors discuss the challenges of providing support for PDAs (Peters et al, 2003;Garrison et al, 2003;Deneen and Arrert, 2003;Spires, 2008;Shipman and Morton, 2001). Deneen and Arrert (2003) note specific challenges to overcome in providing support including, providing a robust wireless infrastructure, the need for students to purchase additional software, and university provided training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several authors discuss the challenges of providing support for PDAs (Peters et al, 2003;Garrison et al, 2003;Deneen and Arrert, 2003;Spires, 2008;Shipman and Morton, 2001). Deneen and Arrert (2003) note specific challenges to overcome in providing support including, providing a robust wireless infrastructure, the need for students to purchase additional software, and university provided training. At Duke University where members of the School of Medicine were surveyed and it was determined there was demand for PDA content, however not providing technical support for PDAs was ultimately decided due to variations in hardware and other challenges (Garrison et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Saeed (2006) indicated that, the growth in new technology‐enhanced learning has raised new research issues for library services, implying that the development of new electronic library technologies to support new educational environments or activities is needed. The study of Deneen and Allert (2003) showed that students became familiar with using hand‐held computers to access digital materials very soon, although the screen resolution of the hand‐held devices was low at that time. Peters et al (2003) further emphasized the potential of library‐supported PDA‐related content and service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cummings et al cited previous studies on the use of PDAs for information seeking (Carney, Koufogiannakis, & Ryan, 2004;Tenopir, King, Clarke, Na, & Zhou, 2007;Spires, 2008); the technical challenges for libraries to support the new technology (Deneen & Allert, 2003;Garrison, Anderson, MacDonald, Schardt, & Thibodeau, 2003;Peters, Dorsch, Bell, & Burnette, 2003;Good, 2007); and changes in physical environments (Cowart, 2006;Duncan, 2006;Evans, 2006;Whelan, 2007;Lever & Katz, 2007) as precursors to their study. Together, these studies form a nucleus of early research on the possibilities, problems, and promises of information use through hand-held devices.…”
Section: Commentarymentioning
confidence: 99%